The optimisation of a proportional solenoid valve design for heavy vehicle active suspension system. (2015) - Meng, Fei; Chen, Huiyan; Liu, Hao; Han, Bing; Nie, Xingfu
This paper presents investigations on the optimisation of a proportional solenoid valve design for active suspension systems in heavy vehicles. The dynamic models of proportional solenoid valve were developed. To provide rapid opening and closing of the valve, expressions for magnetic attraction force, coil temperature, magnet volume, spool velocity and hydraulic force acting on the valve were developed, depending on the dimensions. The collaborative optimisation (CO) method was employed to solve the proportional solenoid valve optimisation problem. The Non-Dominated Sorting Algorithm-II (NSGA-II) method was applied to solve the system level optimisation problem, and the sequence quadratic programming (SQP) was used for the subsystem optimisation solution. The results showed that the volume minimisation was improved by about 25% compared to the unoptimised design. The output pressure response time improved by 2 ms with an overshoot similar to one obtained in unoptimised design. The analysis and accuracy of the optimisation results were verified experimentally.